Probable cutaneous allergic response to subcutaneous heparin - Gupta, S. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Heparin is a heterogeneous mixture of sulfated mucopolysaccharides, commonly used injectable anticoagulant. It is known to cause cutaneous adverse reactions like eczema, erythematous plaques, exfoliative dermatitis and tissuenecrosis. We report a case of probable cutaneous allergic response caused by injection of heparin with an established causality and severity. Thereaction developed after stopping the drug therapy and after the patient had already been discharged. Since heparin is a widely used drug and this reaction can manifest even after the drug therapy has ceased, thorough counseling of the patient is mandatory.
Keywords: Adult; alergije; dermatologija; Drug Hypersensitivity; Eczema; Ekcem; Heparin; Injections, Subcutaneous; Injekcije subkutane; Odrasli; therapy; Zdravila, preobčutljivost; zdravljenje